2019
DOI: 10.1371/journal.pone.0225606
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies against measles and rubella virus among different age groups in Thailand: A population-based serological survey

Abstract: Measles and rubella are highly contagious viral diseases transmitted via respiratory secretions and aerosolized droplets. Thailand has implemented universal vaccination against measles using the monovalent measles (M) or the trivalent measles-mumps-rubella (MMR) vaccine for the past 30 years. Nevertheless, incidence of measles and rubella remains in some parts of the country. We conducted a seroprevalence study to evaluate the antibodies to measles and rubella virus among Thais of all ages and to determine pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
8
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 13 publications
2
8
1
Order By: Relevance
“…For China, although there were differences depending on the survey period and region, the overall reported seropositivity to measles was 80-90%, which is comparable to our results [ 8 ]. In Thailand, aligning with our observations among Thai migrants, Wanlapakorn et al [ 9 ] reported a high seroprotection rate (98.7%) for measles in those aged > 30 years.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…For China, although there were differences depending on the survey period and region, the overall reported seropositivity to measles was 80-90%, which is comparable to our results [ 8 ]. In Thailand, aligning with our observations among Thai migrants, Wanlapakorn et al [ 9 ] reported a high seroprotection rate (98.7%) for measles in those aged > 30 years.…”
supporting
confidence: 91%
“…In young adults, low immunity to measles was observed in this study and other studies conducted in marriage migrants’ countries of origin [ 6 - 9 ]. For Korea, the 2-dose measles-mumps-rubella vaccination rate has been maintained at > 95% since 1996, but immunity to measles in adolescents and young adults was significantly lower (49-70%) than that in older adults [ 10 ].…”
supporting
confidence: 64%
“…It is lower but still comparable to the findings of other studies. This could be due to the older age of volunteers serum collection [3].…”
Section: Discussionmentioning
confidence: 99%
“…A myriad of pathogens may cause the appearance of rash during febrile illness, and reaching a correct diagnosis is often challenging [ 2 , 3 , 4 ]. Some of these pathogens cause diseases identified from the earliest days of civilization, such as measles and syphilis, which have recently shown a trend toward re-emergence in modern communities [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%